2005
DOI: 10.1055/s-2005-864841
|View full text |Cite
|
Sign up to set email alerts
|

Free Muscle Flap Transfer as a Lymphatic Bridge for Upper Extremity Lymphedema

Abstract: There are limited reports in the literature describing the use of muscle or skin pedicle flaps as a lymphatic bridge to treat obstructive lymphedema. This report demonstrates the successful use of a free muscle flap for a circumferential scar of a forearm as treatment for obstructive lymphedema. Lymphatic drainage is demonstrated across the free flap by lymphoscintigraphy postoperatively. This is the first case report using a free muscle flap to reestablish lymphatic flow across an area of obstructive limb lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 12 publications
(24 reference statements)
0
27
0
Order By: Relevance
“…18,[23][24][25][26][27] In addition, vascularized tissue has the potential to restore lymphatic flow by promoting angiogenesis and lymphatic regeneration. 28,29 Evidence of lymphatic regeneration and spontaneous reanastomosis with recipient vessels has been demonstrated, and these events are linked to patterns of vascular endothelial growth factor expression and macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…18,[23][24][25][26][27] In addition, vascularized tissue has the potential to restore lymphatic flow by promoting angiogenesis and lymphatic regeneration. 28,29 Evidence of lymphatic regeneration and spontaneous reanastomosis with recipient vessels has been demonstrated, and these events are linked to patterns of vascular endothelial growth factor expression and macrophage infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several authors have reported small case series demonstrating decreased lymphedema and re-routed lymphatic flow from lymphedematous upper/lower extremities, genitalia, and head and neck sites after free or pedicled flap transposition of other tissues (e.g., muscle or skin). [11][12][13][14] However, despite these anecdotal results, these procedures are now rarely performed due to their unpredictable outcomes.…”
Section: Flap Interpositionmentioning
confidence: 98%
“…A case report of a free muscle fl ap for upper extremity lymphedema showed lymphatic drainage through the fl ap [ 20 ].…”
Section: Muscle Flapsmentioning
confidence: 99%